The Current State of Supply Chain Management and Development of Rural Labor Resources in Kazakhstan - Gulmira Nurzhanova; Madina Beisenova; Ainura Aitymbetova; Alma Kuralbayeva; Dilyara Zhakipbekova; Elmira Zhussipova; Gulmira Issayeva; Zarema Bigeldiyeva (International Journal of Supply Chain Management, 2019)
Labor resources remain the main factor of production and the national wealth of the state, while improving the efficiency of the supply chain management and the use of labor resources is currently the main task of the economy. This is particularly true of labor in agricultural production, because it is this sector that ensures the food stability of the state. Thus, the purpose of this article is to consider the innovative methods of supply chain management and labor regulation, which are applied in agricultural organizations in general and in women's work in particular. To achieve this goal, a set of complementary research methods, statistical and comparative analysis, a systematic approach to the study of economic phenomena and processes were used. This article describes the main approaches to the innovative methods of supply chain management and to labor incentives, aimed at increasing the motivation and interest of employees. A regression model of the human resource potential of the agricultural region was also constructed, which makes it possible to predict changes in the rural labor force in the region.